Optical signal processing for indoor positioning using a-SiCH technology - Vieira, Manuel (2019)
We use the nonlinear property of silicon carbon (SiC) multilayer devices under UV irradiation to design an optical processor for indoor positioning. The transducer combines the simultaneous demultiplexing operation with photodetection and self-amplification. The proposed coding is based on SiC technology. Based on that, we present a way to achieve indoor localization using the parity bits and a navigation syndrome. A representation with a 4-bit original string color message and the transmitted 7-bit string, the encoding and decoding of accurate positional information processes, and the design of SiC navigation syndrome generators are discussed and tested. A visible multilateration method estimates the position of the device using the decoded information received from several noncollinear transmitters. The location and motion information is found by mapping position and estimates the location areas. Since the indoor position of the light-emitting diode light source is known from building floor plans and lighting plans, the corresponding indoor position and travel direction of a mobile device can be determined.